2005
DOI: 10.1088/0264-9381/22/10/018
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide-catalysis bonding for stable optical systems for space

Abstract: Space-based optical systems must be made from lightweight materials which can withstand significant acceleration and temperature changes. Materials such as ZERODUR R , ULE R (Ultra Low Expansion material) and silica are all potentially suitable. Depending on the specific requirements of the optical system and the transmissive or reflective nature of the optical layout these materials can be used by themselves or together to fabricate optical benches. The geometrical layouts of these optical systems are often v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 10 publications
4
153
0
Order By: Relevance
“…where the N p × N p matrix η is given by We give here as an example the results of this procedure when applied to the parameters in (9). The system is stimulated with two independent signals o iSC and o i whose characteristics are shown in table 1.…”
Section: The Measurement Of Dynamical Parametersmentioning
confidence: 99%
“…where the N p × N p matrix η is given by We give here as an example the results of this procedure when applied to the parameters in (9). The system is stimulated with two independent signals o iSC and o i whose characteristics are shown in table 1.…”
Section: The Measurement Of Dynamical Parametersmentioning
confidence: 99%
“…It has been found that after four weeks of curing they have reached their maximum strength [15,17,23]. Investigations were carried out to determine whether heating bonded samples could aid the evaporation or diffusion of additional water and hence further improve bond mechanical loss.…”
Section: Mechanical Loss Of a Hydroxide Catalysis Bondmentioning
confidence: 99%
“…The strength of hydroxide catalysis bonds between different materials such as fused silica, silicon, sapphire, ULE and zerodur have been studied previously [17,20,[31][32][33][34][35][36][37]. A summary of most of the results can be found in Ref.…”
Section: Strength Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was first created by Gwo for use in the Gravity Probe B satellite [36][37][38]. It has since been further developed for use in the construction of ground-and space-based gravitational wave detectors [13,32,33,[39][40][41].…”
Section: Hydroxide Catalysis Bondingmentioning
confidence: 99%